From forensic chemistry: an educational experience - González Graciela A. (Chemistry Teacher International)
The study of forensic chemical analysis not only aids justice in the investigation of accidental or criminal events but also trains chemistry students in analysing hypothetical scenes, such as the design of scientific experiments, and alerting them to potential dangers. In this way, it contributes to generating awareness about safety and security, ethics, and the professional responsibilities of chemists. These, although ambitious, are some of the objectives that have led to the development of this course on Chemical Analysis in Forensic Investigation, whose thematic units and teaching details are developed. This work presents a detailed programme for the Forensic Chemistry course offered at the Faculty of Exact and Natural Sciences at the University of Buenos Aires. It includes examples of activities and bibliography, allowing it to be used as a template for similar courses or to adapt some of the thematic units to other chemistry courses. The suggested bibliography supports the education of both students and educators in the field of forensic chemistry. The incorporation of topics such as fires, explosives, chemical warfare agents (CWA), and environmental crimes aims to develop professional profiles for a new generation of chemists more committed to the societal impact of their work.